2019
DOI: 10.1016/s1474-4422(19)30235-2
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary spastic paraplegia: from diagnosis to emerging therapeutic approaches

Abstract: Hereditary spastic paraplegia (HSP) describes a heterogeneous group of genetic neurodegenerative diseases characterised by progressive spasticity of the lower limbs. The pathogenic mechanism, associated clinical features and imaging abnormalities vary significantly according to the affected gene. Here, we describe the clinical and imaging characteristics of the more common forms of HSP. We discuss how to approach the diagnosis and management of a suspected case of HSP in the era of next generation sequencing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
224
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(233 citation statements)
references
References 115 publications
(141 reference statements)
4
224
2
3
Order By: Relevance
“…1,2 Historically, HSP is distinguished as pure or complicated forms on the basis of clinical grounds. 3 Pure form HSP shows predominant spasticity and weakness restricted to the lower limbs, and often presents hypertonia, hyperreflexia, and Babinski sign. In addition, bladder dysfunction and sensory disturbance are also frequently reported in the pure form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Historically, HSP is distinguished as pure or complicated forms on the basis of clinical grounds. 3 Pure form HSP shows predominant spasticity and weakness restricted to the lower limbs, and often presents hypertonia, hyperreflexia, and Babinski sign. In addition, bladder dysfunction and sensory disturbance are also frequently reported in the pure form.…”
Section: Introductionmentioning
confidence: 99%
“…4 Notably, it has been proposed that many autosomal recessive HSP genes remain unidentified. 3 Recently, loss-of-function mutations in the CAPN1 gene have been described as causative for spastic paraplegia 76 (SPG76). 5 CAPN1 encodes a neutral calcium-activated protease known as calpain-1 protein, which is involved in processes of synaptic plasticity, neuronal migration, neuronal maintenance and necrosis, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of spatacsin function may affect axonal transport, contributing to the degeneration of the corticospinal tract and corpus callosum in HSP [33]. More recently, loss of spatacsin has also been demonstrated to be pivotal for autophagic lysosome reformation, and resulted in depletion of free lysosomes, accumulation of autolysosomes or lipids in lysosomes, and neuronal degeneration [34]. As shown in our study, we have reported four sporadic spastic paraplegias with TCC cases, and found novel SPG11 mutations in each patient by next generation sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…To date, it clearly emerged that HSP, HA, ASS, and other neurological disorders are part of a continuum of overlapping clinical conditions. For instance, the clinical overlap of HSP with HA or intellectual/ developmental disability is not new and so it is the overlap with the mechanisms involved in more common neurological conditions including amyotrophic lateral sclerosis, multiple sclerosis, Parkinson disease, and dementias (Patten et al, 2014;Parodi et al, 2017;Boutry et al, 2019b;Shribman et al, 2019). Since HSP and ASS are a group of disorders characterized by high genetic diversity, researchers have widely exploited the zebrafish as an in vivo model system of these pathologies.…”
Section: Conclusion and Future Applicationsmentioning
confidence: 99%